Source attribution of human Campylobacter isolates by MLST and fla-typing and association of genotypes with quinolone resistance. - Sonja Kittl (Public Library of Science (PLoS), 2013)
Campylobacteriosis is the most frequent zoonosis in developed countries and various domestic animals can function as reservoir for the main pathogens Campylobacter jejuni and Campylobacter coli. In the present study we compared population structures of 730 C. jejuni and C. coli from human cases, 610 chicken, 159 dog, 360 pig and 23 cattle isolates collected between 2001 and 2012 in Switzerland. All isolates had been typed with multi locus sequence typing (MLST) and flaB-typing and their genotypic resistance to quinolones was determined. We used complementary approaches by testing for differences between isolates from different hosts with the proportion similarity as well as the fixation index and by attributing the source of the human isolates with Bayesian assignment using the software STRUCTURE. Analyses were done with MLST and flaB data in parallel and both typing methods were tested for associations of genotypes with quinolone resistance. Results obtained with MLST and flaB data corresponded remarkably well, both indicating chickens as the main source for human infection for both Campylobacter species. Based on MLST, 70.9% of the human cases were attributed to chickens, 19.3% to cattle, 8.6% to dogs and 1.2% to pigs. Furthermore we found a host independent association between sequence type (ST) and quinolone resistance. The most notable were ST-45, all isolates of which were susceptible, while for ST-464 all were resistant.